The Influence of E-WOM and Perceived Ease of Use on Purchase Interest in Muslim Fashion Products with Trust as an Intervening Variable (Study on Shopee Users in Surakarta City) - Hardhianti, Vioreliana; Sholahuddin, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to investigate the impact of Electronic Word of Mouth (E-WOM) and Perceived Ease of Use on the Purchase Intention of Muslim fashion products, with Trust as an Intervening Variable. The study was conducted on Shopee platform users in Surakarta City. This research method uses a quantitative approach by collecting data through an online survey of Shopee users who are interested in Muslim fashion products. Data analysis was carried out using statistical tests and regression to evaluate the relationship between the variables studied. The results showed that the E-WOM variable had a positive and significant effect on trust and buying interest in Muslim fashion products at Shopee.